Inventory and supply chain strategies - Song, Jing-Sheng (Henry Stewart Talks, 2012)
What is a supply chain, Role of inventory in supply chains, Fundamental inventory control policies, concepts, and laws, EOQ formula, Newsvendor model, Base-stock policy, Reorder-point, Order quantity policy, ABC analysis, Safety stock, Inventory position, Echelon stock, Internal fill rate, Basic principles for managing inventory to gain competitive advantage, Risk pooling, Risk sharing, Information sharing, Reallocation of decision rights, Capacity and inventory tradeoffs, Matching supply chain capability with product features, Successful supply chain innovations, Cross-docking, Quick response, Accurate response, Vendor managed inventory, Postponement, Assemble-to-order, Economies of scarcity
Reviewed at 2020/10/29